Action research – conceptual distinctions and confronting the theory–practice divide in Lesson and Learning Studies. Issue 4 (8th August 2019) - Posch, Peter
ABSTRACT: The first part of the paper positions the action research movement in the context of other research and development concepts and describes its rationale and some basic quality criteria. Action research is regarded as an umbrella term defined by two generic characteristics: substantial practitioner control of both the practice situation investigated and the research process. These characteristics leave space for considerable variation of action research approaches, depending on the values the two defining criteria take. Selected approaches are described. In the second part, two far-eastern examples of action research are selected that are rapidly gaining ground in western countries: Lesson and Learning Studies. They appear to have potential to not only provide access to practical, mostly tacit routines but to also contribute to reconverting informed knowledge into practical knowledge. A shared characteristic of Lesson and Learning Studies, the iteration of cycles of action and reflection, could be, among other factors, responsible for this transformation. The possible contribution of this feature to overcome the theory–practice divide is discussed.